Modern Interpretation Of Vascular Dementia - Rakhimbaeva G.S; Kamilova M.R (Genius Journals, 2023)
The proportion of elderly people in the total population is increasing, so that the problem of psychopathology in adulthood is becoming more and more clinical and social. It is known that this, in turn, concerns vascular dementia and the following risk factors that cause it: cardiovascular disease, arterial hypertension, stroke and diabetes are all good for older people and older people.
Keywords: Vascular dementia; cognitive disorders; dementia